2011
DOI: 10.1063/1.3592831
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic thermopower and magnetothermopower in a misfit-layered calcium cobaltite

Abstract: An unusual anisotropy of thermopower and magnetothermopower has been observed in the powerful thermoelectric Ca3Co4O9+δ single crystal. The in-plane thermopower is about twice as big as the out-of-plane thermopower. Combining ab initio band structure calculation with semiclassical model analysis, we understand this anisotropy with band structure effects and especially with anisotropic Fermi surface. We find that a strong anisotropy in the topology of Fermi surface leads to the anisotropy of (magneto)thermopowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 26 publications
4
17
0
Order By: Relevance
“…24,35,36 To some extent, this is due to the computational challenge posed by modeling an incommensurate crystal. Asahi et al carried out the first ab initio calculations on CCO within the framework of density functional theory (DFT): Using an approximate unit cell of composition (Ca 2 CoO 3 ) 4 (CoO 2 ) 6 , they performed a comprehensive study of the structural, electronic, magnetic, and thermoelectric properties of CCO.…”
Section: Introductionmentioning
confidence: 99%
“…24,35,36 To some extent, this is due to the computational challenge posed by modeling an incommensurate crystal. Asahi et al carried out the first ab initio calculations on CCO within the framework of density functional theory (DFT): Using an approximate unit cell of composition (Ca 2 CoO 3 ) 4 (CoO 2 ) 6 , they performed a comprehensive study of the structural, electronic, magnetic, and thermoelectric properties of CCO.…”
Section: Introductionmentioning
confidence: 99%
“…1 shows enlarged (002) and (004) diffraction peaks to illustrate the effects of Ni, Ce co-doping on the Ca 3 Co 4 O 9 þ δ lattice. Given that Ca 3 Co 4 O 9 þ δ consists of two alternating subsystems of a CoO 2 sheet and a distorted rock-salt type Ca 2 CoO 3 block [8], Co cations in the CoO 2 sheet include a mixture of Co 3 þ (0.54 Å) and Co 4 þ (0.53 Å). By contrast, Co in the Ca 2 CoO 3 block mainly presents as Co 2 þ with 0.74 Å ionic radius.…”
Section: Methodsmentioning
confidence: 99%
“…Since Terasaki et al [2] reported that NaCo 2 O 4 features large thermopower and high electrical conductivity, layered cobalt oxides have been studied extensively [3][4][5]. Ca 3 Co 4 O 9 þ δ is considered a promising p-type thermoelectric material candidate because of its large thermopower, metallic conductivity, and chemical stability at high temperatures [6][7][8]. Ca 3 Co 4 O 9 þ δ is a typical layered cobalt oxide; it consists of two alternating subsystems of a CoO 2 sheet and a distorted rock-salt type Ca 2 CoO 3 block stacked along the c-axis [3].…”
Section: Introductionmentioning
confidence: 99%
“…3 and 14, the rock-salt subsystem mainly shortens the phonon mean free path and thus lowers the thermal conductivity, while the hexagonal subsystem is responsible for the electrical conductivity. In addition, the magneto-transport properties are remarkable [2,10,17]; in particular, a high-temperature (above 600 K) spin state transition has been discovered very recently [36,37].…”
Section: Introductionmentioning
confidence: 99%